On The Stability of the Approximate Solution of the Galerkin Method for A Parabolic Boundary Problem with Divergent Main Part - Mamatov Alisher Zulunovich1, Turdibayev Dilshod Xamidovich2, Nafasov Ganisher Abdurashidovich2 Davlatov Utkir Tagayevich3, Komilov Mirziyo Mirkomilovich3 (Zien Journals, 2022)
The article considers the application of the Galerkin method to the solution of boundary value problems of parabolic type with a divergent main part, when the boundary condition contains the time derivative of the desired function
Keywords: Boundary value problem, quasilinear equation, boundary condition, Galerkin method, generalized solution, parabolic problem, approximate solution, error estimate, monotonicity, inequalities, time derivative, boundary, region, scalar product, norm, continuity, desired function